An improved configuration of lignite pre-drying using a supplementary steam cycle in a lignite fired supercritical power plant. (15th December 2015) - Xu, Cheng; Xu, Gang; Zhao, Shifei; Zhou, Luyao; Yang, Yongping; Zhang, Dongke
Highlights: An improved lignite pre-drying using a supplementary steam cycle is proposed. Thermodynamic and economic analyses are quantitatively conducted. Lower exergy destruction and better matched energy level are obtained. Higher energy efficiency improvement and greater economic benefits are achieved. Abstract: A novel concept of improved configuration of lignite pre-drying using a supplementary steam cycle incorporated in a lignite fired supercritical power plant was proposed in this study. Differing from the conventional lignite pre-drying power plant configuration, in this lignite pre-drying power plant (LPDPP) concept, the steam bleeds for the dryer and some regenerative heaters (RHs) are redirected from the high pressure turbines and low pressure turbines through a separate turbine named the Regenerative-turbine (R-turbine). With the R-turbine in place, the degree of super-heating of the bleeds for the dryer and for RH3–RH5 is significantly reduced, thus leading to a reduction in the heat transfer temperature difference and exergy destruction rate. The net energy efficiency and the economic benefits of the proposed LPDPP are also enhanced as compared to the conventional configuration. The analysis showed that, for a 600 MW supercritical LPDPP, the exergy destruction of the dryer could be reduced from 14.23 MWth in the conventional configuration to 13.25 MWth in the proposed design. The net energy efficiency could be further improved by 0.3 percentages points with a heat rate reduction of approximately 59.4 kJ/kW h. The net economic benefit of the proposed LPDPP could reach $47.6 M per year, which is $0.9 M greater than that of the conventional lignite pre-drying unit.